Bias-dependent degradation of various solar cells: lessons for stability of perovskite photovoltaics. Issue 2 (21st January 2019) - Khenkin, Mark V.; K. M., Anoop; Katz, Eugene A.; Visoly-Fisher, Iris
Abstract : Understanding degradation mechanisms in halide perovskite solar cells is the key aspect to achieve a breakthrough in photovoltaics. Abstract : Understanding device instability mechanisms in halide perovskite solar cells (PSCs) is the key aspect to achieve a breakthrough in photovoltaics. One of the puzzling questions in this regard is electrical bias-dependent degradation of PSCs. Several mechanisms have been suggested to explain the effect, but none are sufficient to embrace all observations. Bias-dependent degradation has been observed in several types of previously developed solar cells, and was attributed to a variety of underlying mechanisms. For example, extrinsic and intrinsic migration of mobile ionic species, which are widely believed to be one of the main reasons for PSC instability, were known to instigate degradation of CdTe and CI(G)S-based photovoltaics. Yet, the stability of these types of solar cells was greatly improved by rational design and currently meets the requirements of in-field applications. In this paper we review the progress in the understanding of bias-dependent instabilities in different photovoltaic technologies (including perovskites) and discuss what lessons can be learned to improve the PSC stability.